(untitled) (Eurasian Medical Research Periodical, 2022)
The role of spiritual factors in the development of ideal immunity in adolescents. The author focuses on the spiritual factors of the problem. In particular, the role of spiritual values in enhancing the spiritual qualities of young people is analyzed.